PELATIHAN PEMBUATAN DAN PENGELOLAAN BLOG DESA PADA PERANGKAT DESA CAMPURSARI KECAMATAN MEGANG SAKTI - Lucy Asri Purwasi; Denny Alfian; As Elly S; Rani Refianti; Maria Lutfiana (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
The purpose of this activity is to train the skills and knowledge of village officials in using blogs to share information regarding programs implemented in the village of Campursari. The training participants were attended by 15 people with 2 of them acting as operators. The methods that will be carried out in this activity, namely the lecture method, mentoring, practice and demonstration. The implementation of this activity showed a positive response and high enthusiasm from the participants. The results of the questionnaire show that each of the indicators of knowledge and how to use related to blogs reaches a percentage of 85% with the criteria of very knowing and the indicator of Interest in training activities and further training regarding blogs shows a percentage of 100% with the criteria of being very interested. So that with the training and management of this blog it is hoped that it will be able to better introduce the village's potential both from its natural resources (SDA), the economy, education and health sectors as well as government programs to develop Campursari Village to outside communities.